Evaluation of riverine suspended particulate matter sampling with sedimentation boxes and flow-through centrifuges for total mercury and methylmercury analysis - Stephan Krisch; Alexandra Alten; Lorenz Gfeller; Andreas Breidenbach; Jens Hahn; Lars Duester; Harald Biester; Jan G. Wiederhold (Environmental Research, 2026)

Prospective life cycle assessment of cost-effective pathways for achieving the FuelEU Maritime Regulation targets - Anna Ingwersen; Alvaro J. Hahn Menacho; Stephan Pfister; Jonathan N. Peel; Romain Sacchi; Christian Moretti (Science of The Total Environment, 2025)

Phylogeographic structure and population connectivity of a small benthic fish ( Tripterygion tripteronotum ) in the Adriatic Sea - Kristina M. Sefc; Maximilian Wagner; Lukas Zangl; Sara Weiß; Bernd Steinwender; Paul Arminger; Theresa Weinmaier; Nejra Balkic; Tobias Kohler; Silvio Inthal; Marcelo Kovačić; Stamatis Zogaris; et al. (Journal of Biogeography, 2020)
Aim Population connectivity of benthic marine organisms depends strongly on planktonic larval dispersal and is controlled by geographic distance and oceanographic structure. We examine isolation by distance versus resistance to barriers (ocean current boundaries) against a background of post‐glacial habitat expansion in a small benthic fish of the Adriatic Sea. Location Adriatic Sea, Eastern Mediterranean. Taxon Tripterygion tripteronotum . Methods We performed population genetic analyses using mitochondrial control region sequences of 550 individuals from 25 locations sampled along the Eastern Adriatic coast. Investigations of population structure included differentiation tests, cluster analyses and distance‐based redundancy analysis. We then ran Lagrangian simulations of passive larval drift to examine correlations among population structure, geographic distance and the Adriatic gyre system. To test for signatures of a post‐glacial range expansion, we modelled the demographic history of the populations and examined the geographic distribution of genetic diversity. Results Genetic population structure corresponded to the Adriatic gyres without additional effect of geographic distance. Inference of northward‐biased gene flow between the northern and the Istrian gyre was consistent with simulated trajectories of passive drift, whereas the phylogeographic break coinciding with the boundary between the Central and the Northern Adriatic gyre was stronger than predicted by drift simulations. Genetic connectivity of populations within gyres was high. Genetic signatures of population expansion were consistent with a rapid post‐glacial recolonization of the northern Adriatic. Main conclusions The combination of dense sampling and passive drift simulation allowed us to distinguish among effects of geographic distance, oceanographic features and palaeoenvironmental changes on current population structure. Comparisons between realized and potential connectivity illustrate the value of integrating different data sources to understand population structure and inform conservation planning.

Wood anatomy variability under contrasted environmental conditions of common deciduous and evergreen species from central African forests - Yegor Tarelkin; Koen Hufkens; Stephan Hahn; Jan Van den Bulcke; Jean-François Bastin; Bhely Angoboy Ilondea; Olivier Debeir; Joris Van Acker; Hans Beeckman; Charles De Cannière (Trees, 2019)

Expression and function of Anoctamin 1/TMEM16A calcium-activated chloride channels in airways of in vivo mouse models for cystic fibrosis research - Anne Hahn; Johanna J. Salomon; Dominik Leitz; Dennis Feigenbutz; Lisa Korsch; Ina Lisewski; Katrin Schrimpf; Pamela Millar-Büchner; Marcus A. Mall; Stephan Frings; Frank Möhrlen (Pflügers Archiv - European Journal of Physiology, 2018)

Unveiling of miRNA Expression Patterns in Purkinje Cells During Development - Lukas Pieczora; Lara Stracke; Matthias Vorgerd; Stephan Hahn; Carsten Theiss; Verena Theis (The Cerebellum, 2017)

Suppression of soluble adenylyl cyclase protects smooth muscle cells against oxidative stress-induced apoptosis - Sanjeev Kumar; Avinash Appukuttan; Abdelouahid Maghnouj; Stephan Hahn; H. Peter Reusch; Yury Ladilov (Apoptosis, 2014)

Comparative microarray analysis of microRNA expression profiles in primary cutaneous malignant melanoma, cutaneous malignant melanoma metastases, and benign melanocytic nevi - Michael Sand; Marina Skrygan; Daniel Sand; Dimitrios Georgas; Thilo Gambichler; Stephan A. Hahn; Peter Altmeyer; Falk G. Bechara (Cell and Tissue Research, 2013)

Retraction Note: Latitude affects degree of advancement in laying by birds in response to food supplementation: a meta-analysis - Stephan J. Schoech; Thomas P. Hahn (Oecologia, 2012)

Prevalence of BRCA2 and CDKN2a mutations in German familial pancreatic cancer families - Emily P. Slater; Peter Langer; Volker Fendrich; Nils Habbe; Brunhilde Chaloupka; Elvira Matthäi; Mercedes Sina; Stephan A. Hahn; Detlef K. Bartsch (Familial Cancer, 2010)

Variation of territory size and defense behavior in breeding pairs of the endemic Lake Tanganyika cichlid fish Variabilichromis moorii - Christian Sturmbauer; Christoph Hahn; Stephan Koblmüller; Lisbeth Postl; Danny Sinyinza; Kristina M. Sefc (Hydrobiologia, 2008)

RETRACTED ARTICLE: Latitude affects degree of advancement in laying by birds in response to food supplementation: a meta-analysis - Stephan J. Schoech; Thomas P. Hahn (Oecologia, 2008)

Food supplementation and timing of reproduction: does the responsiveness to supplementary information vary with latitude? - Stephan J. Schoech; Thomas P. Hahn (Journal of Ornithology, 2007)

Low Frequency of CHEK2 Mutations in Familial Pancreatic Cancer - Detlef K. Bartsch; Kristina Krysewski; Mercedes Sina-Frey; Volker Fendrich; Harald Rieder; Peter Langer; Ralf Kress; Margarete Schneider; Stephan A. Hahn; Emily P. Slater (Familial Cancer, 2006)